2018
DOI: 10.1177/2515841418817490
|View full text |Cite
|
Sign up to set email alerts
|

Choroideremia: from genetic and clinical phenotyping to gene therapy and future treatments

Abstract: Choroideremia is an X-linked inherited chorioretinal dystrophy leading to blindness by late adulthood. Choroideremia is caused by mutations in the CHM gene which encodes Rab escort protein 1 (REP1), an ubiquitously expressed protein involved in intracellular trafficking and prenylation activity. The exact site of pathogenesis remains unclear but results in degeneration of the photoreceptors, retinal pigment epithelium and choroid. Animal and stem cell models have been used to study the molecular defects in cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 130 publications
(327 reference statements)
1
51
0
Order By: Relevance
“…At this time, the visual acuity deteriorates. [1][2][3][4][5] Choroideremia is a progressive disease, which explains the latest stage of the disorder of the current 58-yearold Brazilian patient compared with the 34-year-old Cuban descendent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At this time, the visual acuity deteriorates. [1][2][3][4][5] Choroideremia is a progressive disease, which explains the latest stage of the disorder of the current 58-yearold Brazilian patient compared with the 34-year-old Cuban descendent.…”
Section: Discussionmentioning
confidence: 99%
“…4 Until now, according to the literature, there has not been any genotype-phenotype correlation in choroideremia. 1,[15][16][17][18][19] Sanger sequencing of all CHM exons and exon/intron boundaries found only one synonymous variant (c.1359C>T, p.(Ser453=)). This variant was considered to have a high likelihood of being disease-causing, via the observed skipping of CHM exon 11 reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 In addition, REP1 is heavily involved in intracellular trafficking of proteins, small substrates, and various organelles. 4 Mutations in the CHM gene subsequently alter the function of REP1, causing degeneration in cellular structure, transport, and stability. The mechanism of disease pathophysiology remains unclear, as it is uncertain whether the RPE, choroid, or photoreceptor layers are affected first or simultaneously; however, it has been suggested that the RPE may be affected first, leading to retinal disturbances and to the formation of retinal tubulations.…”
Section: Introductionmentioning
confidence: 99%